2014
DOI: 10.1089/sur.2012.177
|View full text |Cite
|
Sign up to set email alerts
|

Co-Existence of Hepatocellular Carcinoma and Hepatic Tuberculosis

Abstract: Through this case report, the authors discuss the pathogenesis of the rare association of TB and malignant neoplasm of the liver, and present a review of the current literature on the association of TB and cancer. Further research is required to determine whether a TB infection resembles other chronic infections and inflammatory conditions in having a potential to facilitate oncogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Currently, there have only been four other known cases of such synchronous presentations in the same patient. 5 , 6 More often, HTB is diagnosed during the work-up for a suspected HCC during histological evaluation. It also seems unlikely for tuberculosis to contribute to the pathogenesis of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there have only been four other known cases of such synchronous presentations in the same patient. 5 , 6 More often, HTB is diagnosed during the work-up for a suspected HCC during histological evaluation. It also seems unlikely for tuberculosis to contribute to the pathogenesis of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have implicated AFP in the regulation of cell growth, differentiation, apoptosis, angiogenesis, and immune regulation [47]. A few previous studies reported normal AFP in TB patients, but increased AFP in TB patients with hepatocellular carcinoma [48,49]. Monocytes can undergo homotypic fusion to produce different types of multinucleated giant cells in response to M. tuberculosis infection.…”
Section: Discussionmentioning
confidence: 99%
“…The simultaneous occurrence of TB with HCC on the background of hepatitis C virus (HCV) has been rarely reported owing to potent anti-tubercular treatment nowadays. 57 We hereby report such a case.…”
Section: Introductionmentioning
confidence: 87%